Effect of Biscuits Enriched with Bilih Fish (Mystacoleucus padangensis) on Growth of Experimental Rats - Diana, Fivi Melva; Rimbawan, Rimbawan; Damayanthi, Evy; Dewi, Mira; Juniantito, Vetnizah; Lipoeto, Nur Indrawaty (Jurnal Gizi dan Pangan, 2020)
The research aimed to produce biscuits formulated with Bilih fish and to analyse the effect of Bilih-fish-based biscuits on the growth of experimental rats. Six biscuit formulas were developed using three different amounts of Bilih fish flour (0 g, 20 g, and 30 g added to one formula dough) and two flavors (chocolate and vanilla). One biscuit formula was selected based on the best organoleptic test. Four treatments were applied to 24 male growing rats (21 day olds of the Spraque Dawley strain) for 28 days using a completely randomized design study. The treatments used were P1 (standard feed), P2 (standard feed + standard biscuits), P3 (standard feed + standard biscuits + pure omega-3 oil) and P4 (standard feed + the best formula biscuit). The parameters measured on rats were weight and tail length. The best formula biscuit based on the organoleptic test was the chocolate-flavor biscuits prepared with 20 g Bilih fish flour. The longest tail length was found in the P4 treatment (2,257±0.52 cm), which was significantly longer than the P2 (1.46±0.34 cm) and P1 (1.34±0.29 cm) treatments. No significant weight differences were found among the rats in all treatments. Hence, the chocolate-flavor biscuits formulated with the addition of 20 g Bilih fish flour increased the linear growth in experimental rats as shown by the significant difference in the tail lengths found in the treatment group.